Teen Pregnancy in Roman and Egyptian Communities - Terolli, Lindita (Richtmann Publishing, 2012)
The aim of this study is the identification of people in need, to pay more attention to them and to inform for preventing healthcomplications. Material and methods: The study was conducted through the examinations of patients in the maternity of Korca and thequestionnaires were designed to detect the level of knowledge, which had the population under study, with regard to family planning,care and examinations that should be performed during pregnancy, for the pregnancy pathologies and pregnancies at risk. Results areexpressed in % (in relation to age, skin color, level of knowledge about the problems above. Were questioned 200 women of whom 100were girls and women of Roman and Egyptian communities and belonged to age 13-18. It was compared their culture on health (amongwhite adolescents and Roman and Egyptian). The information about the study was collected during a period of years (2008-20011).Conclusions: Girls whose age belonged to adolescence had incomplete information with regard to the reproduction health, among themRomans and Egyptian had little or no information to. Despite Proficiency Testing found in textbooks or in the information provided in thepress and other media means, it’s emphasized the absence of knowledge. Complications not related only to abortion but also presentduring pregnancy and during birth. Babies born hypotrophe is another complication.